Marginal Microleakage Detection and Radiopacity Measurement under Restoration with Conventional and Digital Radiography - Yufa, Salsabila; Shantiningsih, Rurie Ratna; Suryani, Isti Rahayu (UI Scholars Hub, 2019)
Objective: Marginal microleakage detection is performed to prevent secondary caries. The present study aimed to determine the difference in the accuracy between conventional and digital radiography methods in detecting marginal microleakage and the radiopacity measurement of restoration material. Methods: We used 44 anterior maxillary teeth after extraction that had been filled with class III glass ionomer cement and then planted in paraffin wax blocks. These samples were then systematically exposed using conventional and digital indirect periapical radiography techniques. Microleakage detection was measured using three marginal microleakage scales. The level of radiopacity of restoration material was measured using ImageJ software and calculated using the standard radiopacity value calculation formula. All data were analyzed using the Mann–Whitney U test. Results: Outcome data demonstrated that there was no difference (p = 0.6) between the two radiography techniques in detecting mi- croleakage of restoration. However, radiopacity measurements revealed a significant difference (p = 0.0) between these two radiography techniques in their ability to determine radiopacity. Conclusion: The results suggest that there is no difference between conventional and digital indirect periapical radiography techniques in detecting microleakage of restoration material; however, a high radiopacity level was found from the digital indirect radi- ography technique.